Design, synthesis, and antitumor activity of novel sorafenib derivatives. (20th January 2022) - Hou, Mi; Zou, Ya‐Yu; Fan, Si‐Li; Li, Xiao‐Qin; Shao, Li‐Hui; Li, Zhu‐Rui; Chen, Dan‐Ping; Wang, Zhen‐Chao; Ouyang, Gui‐Ping
Abstract: New series of 18 compounds were synthesized using sorafenib derivatives as parent structure and p ‐aminoacetophenone as raw materials. The structures of the newly synthesized compounds were confirmed on the basis of 1 H, 13 C NMR and HRMS (Supporting Information). Their antitumor activities against human lung adenocarcinoma cells A549 (A549), prostate cancer cells PC‐3 (PC‐3), human chronic myeloid leukemia cells (K562), and human liver cancer cells (HepG2) in vitro were evaluated, using Sorafenib as a positive control drug. Bioactivity assays indicated that these compounds showed good antitumor activities toward tested four cancer cell lines. In particular, compound 7n showed potent inhibitory activity with IC50 of 7.39 ± 1.51 μM toward K562. The mechanism and the apoptosis inducing effect of 7n against k562 cell line were studied. The results showed that compound 7n blocked K562 cells in G2/M phase to induce cell apoptosis with a concentration and time‐dependent manner. Abstract : New series of 18 compounds were synthesized using sorafenib derivatives as parent structure and p‐aminoacetophenone as raw materials. Bioactivity assays indicated that these compounds showed good antitumor activities toward tested four cancer cell lines. The results showed that compound 7n blocked K562 cells in G2/M phase to induce cell apoptosis with a concentration and time dependent manner.